Ternary cathode material with core-shell structure and preparation method and application thereof

By using core-shell structure and low-temperature combustion method in ternary positive electrode materials, the problems of unstable material structure and insufficient cladding performance are solved, higher mechanical strength and conductive properties are achieved, resource waste is avoided, and battery Battery life and safety.

CN114665077BActive Publication Date: 2025-01-10GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210317193.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-29
Publication Date
2025-01-10
Estimated Expiration
2042-03-29

AI Technical Summary

Technical Problem

The layered structure of the existing ternary positive electrode materials is unstable and is prone to collapse and break during charging and discharging. It is difficult for traditional coating agents to take into account both electron-conducting and ion-conducting properties, resulting in waste of resources and environmental pollution.

Method used

The ternary positive electrode material adopts a core-shell structure, the core layer is LiNixCoyMnzO2 and the shell layer is LidMO. Through low-temperature combustion method and spray coating technology, the mechanical strength and conductive properties of the material are improved to avoid direct scrapping of micro powder.

Benefits of technology

It improves the mechanical strength of the material and the ion-conducting and electron-conducting properties, extends the life, avoids resource waste and environmental pollution, and improves the capacity and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114665077B_ABST
    Figure CN114665077B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials, and discloses a core-shell structured ternary positive electrode material and a preparation method and application thereof. The chemical formula of the ternary positive electrode material is LiNi x Co y Mn z O 2 ·wLi d MO; M is (Ni a Co b Mn c ) k A 1‑k , A includes at least one of cobalt, cerium, nickel, manganese, aluminum, zirconium, strontium, and yttrium; wherein 0.3≤x≤1, y>0, z>0, and x+y+z=1, 0.3≤a≤1, b≥0, c≥0, and a+b+c=1, 1≤d≤3, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a ternary positive electrode material with a core-shell structure and a preparation method and application thereof. Background Art

[0002] In the field of electric vehicles, people are generally concerned about the range of electric vehicles. With the occurrence of various electric vehicle spontaneous combustion incidents, people are also paying more and more attention to the safety performance of electric vehicles. The most critical component of electric vehicles is the lithium-ion battery. Lithium-ion batteries are generally composed of positive electrodes, negative electrodes, diaphragms and electrolytes. The performance of the positive electrode material directly determines the energy density, safety performance and service life of lithium-ion batteries. At present, lithium-ion battery positive electrodes generally use lithium-ion compounds, such as LiMn 2 O 4 、LiFePO 4 、LiCoO 2 、Ternary cathode material Li(Ni x Co y Mn z ) 2 Among them, ternary cathode materials have become the research focus of major battery manufacturers because of their higher energy density advantage. However, the layered structure of ternary cathode materials is unstable, and the structure is prone to collapse and break during repeated charge and discharge processes. The exposed fresh electrode is easily corroded by the electrolyte, so other modification methods are needed to stabilize its structure. Among them, coating is a relatively common and effective method.

[0003] Traditional coating agents include metal oxides, graphene, phosphates, and conductive polymers, but their functions are relatively simple, and it is difficult to have both electronic and ion conductivity, and it is difficult to provide high capacitance and rate performance. In addition, the industrial production of ternary cathode materials will produce a considerable amount of crushed micropowders, which are ternary materials with abnormal particle size and a certain capacity. Directly scrapping them will cause certain resource waste, environmental pollution, and economic losses. Therefore, the secondary use of micropowder crushed materials will produce obvious economic and social benefits. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a core-shell structured ternary positive electrode material and its preparation method and application. The material is a core-shell structure, which improves the mechanical strength of the material. The shell layer can effectively protect the core layer substrate from being easily corroded by the electrolyte. Due to the introduction of positive electrode micropowder, the shell layer has significantly better ion and electron conductivity, and the capacity and rate performance are improved to a certain extent.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A core-shell structured ternary cathode material, the chemical formula of which is LiNi x Co y Mn z O 2 ·wLi d MO, the core layer of the core-shell structured ternary positive electrode material is LiNi x Co y Mn z O 2 , the shell is Li d MO; wherein M is (Ni a Co b Mn c ) k A 1-k , wherein A includes at least one of cobalt, cerium, nickel, manganese, aluminum, zirconium, strontium, and yttrium; wherein 0.3≤x≤1, y>0, z>0, and x+y+z=1, 0.3≤a≤1, b≥0, c≥0, and a+b+c=1, 1≤d≤3, 0 <k≤0.5,0.01%≤w≤2%。

[0007] Preferably, in the core-shell structured ternary positive electrode material, the value of x is 0.3≤x≤0.6, and the value of a is 0.6≤a≤0.8.

[0008] Preferably, the core-shell structured ternary cathode material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 0.001[LiNi 0.5 Co 0.2 Mn 0.3 O 2 ·Li 2 (Co 2 Ce)O 8 ]、LiNi 0.8 Co 0.1 Mn 0.1 O 2 0.002[LiNi 0.5 Co 0.2 Mn 0.3 O 2 ·Li 2 (Co 2 Ce)O 8 ]、LiNi 0.8 Co 0.1 Mn 0.1 O 2 0.005[LiNi 0.5 Co 0.2 Mn 0.3 O 2 ·Li2 (Co 2 Ce)O 8 ] at least one of ].

[0009] A method for preparing a core-shell structured ternary cathode material comprises the following steps:

[0010] (1) dispersing the positive electrode powder into an organic solvent, grinding it, adding nitrate, organic acid and surfactant, stirring and emulsifying it to obtain an emulsion;

[0011] (2) evaporating and drying the emulsion to obtain a fluffy porous dry gel, and heating and igniting the dry gel to obtain a fluffy composite oxide;

[0012] (3) The composite oxide is dispersed in an organic dispersion, mixed, spray-coated on a ternary substrate, and calcined to obtain a core-shell structured ternary cathode material.

[0013] Preferably, in step (1), the positive electrode fine powder is a positive electrode material with abnormal particle size produced in the process of producing the positive electrode material, and is an industrial by-product.

[0014] Preferably, in step (1), the positive electrode fine powder is at least one of a ternary positive electrode fine powder and a lithium iron phosphate fine powder.

[0015] Further preferably, the chemical formula of the ternary positive electrode powder is LiNi a Co b Mn c O 2 , where 0.3≤a≤1, b≥0, c≥0, and a+b+c=1. When b and c=0, the chemical formula of the above-mentioned ternary positive electrode powder is LiNiO 2 , which is lithium cobalt oxide powder.

[0016] Preferably, in step (1), the organic solvent is at least one of n-octane, n-heptane, dodecane, ethanol and acetone.

[0017] Preferably, in step (1), the solid-liquid ratio of the organic solvent to the positive electrode fine powder is (0.1-100) mL: 1 g.

[0018] Preferably, in step (1), the grinding method is one of wet grinding, ball milling, air flow milling and mechanical milling.

[0019] Principle: Wet grinding means that the material enters the grinding chamber under the action of the feed pump, and the high-speed rotation of the eccentric disk of the stirring shaft drives the material and the grinding medium to have efficient relative movement. The solid particles of the material are effectively dispersed, sheared and ground. After passing through the dynamic large-flow rotor gap separation filter, a narrow-particle dispersion is obtained. When the feed particle size is less than 450μm, the discharge particle size can reach less than 1μm.

[0020] Preferably, in step (1), the grinding time is 0.1 h to 6 h.

[0021] Preferably, in step (1), the rotation speed of the stirring eccentric disk is 500 to 4000 rpm.

[0022] Preferably, in step (1), the D50 of the positive electrode fine powder is 0.1-1 μm, and the D99 is 0.3-2 μm.

[0023] Preferably, in step (1), the nitrate is at least one of cobalt nitrate, nickel nitrate, manganese nitrate, cerium nitrate, aluminum nitrate, zirconium nitrate, lithium nitrate and strontium nitrate.

[0024] Preferably, in step (1), the surfactant is at least one of hexamethylenetetramine, sodium dodecylbenzenesulfonate, and hexadecyltrimethylammonium bromide.

[0025] Preferably, in step (1), the organic acid is one of lithium acetate and citric acid.

[0026] Preferably, in step (1), the mass ratio of the nitrate: (organic acid or organic acid + surfactant) is (0.1-10):1.

[0027] Preferably, in step (1), the mass ratio of the nitrate to the positive electrode fine powder is (1-100):1.

[0028] Preferably, in step (2), the evaporation temperature is 60-95°C.

[0029] Preferably, in step (2), the drying temperature is 100 to 150° C., and the drying time is 12 to 48 hours.

[0030] Preferably, in step (2), the temperature of the heating and ignition is 200-400° C., and the atmosphere of the heating and ignition is air.

[0031] Low-temperature Combustion Synthesis (LCS) refers to the use of metal nitrates (oxidants) and organic substances such as citric acid, urea, etc. (reducing agents) as reactants, igniting the reactant system at a suitable temperature, causing violent combustion within a few seconds, producing a large amount of gas, and obtaining fluffy ultrafine oxides. The low-temperature combustion method has the advantages of low energy consumption, high product purity and greater product activity.

[0032] The reaction equation of step (2) is:

[0033] LiNi x Co y Mn (1-x-y) O 2 +4Co(NO 3 ) 2 6H 2 O+2Ce(NO 3 ) 3 6H 2 O+2C 6 H 8 O 7 +2C 2 H 3 LiO 2 +C 6 H 12 N 4 +14O 2 →LiNi x Co y Mn (1-x-y) O 2 ·Li 2 (Co 2 Ce)O 6 +Co 2 O 3 +CeO 2 +2N 2 +6NO+8NO 2 +22CO 2 +47H 2 O.

[0034] Preferably, in step (3), the chemical formula of the ternary substrate is LiNi x Co y Mn z O 2 , where 0.3≤x≤1, y>0, z>0, and x+y+z=1.

[0035] Preferably, in step (3), the organic dispersion is at least one of a polyacrylamide solution, a hydrolyzed polymaleic anhydride solution, a polyethylene glycol 200 solution, and a polyethylene glycol 400 solution.

[0036] Preferably, in step (3), the concentration of the organic dispersion is 0.01 to 2 g / mL.

[0037] Preferably, in step (3), the concentration of the composite oxide is 0.01 to 0.5 g / mL, and the ultrasonic time is 0.1 to 5 h.

[0038] Preferably, in step (3), the composite oxide is dispersed in an organic dispersion and mixed to obtain a composite oxide suspension; the liquid-to-solid ratio of the composite oxide suspension to the ternary substrate is (0.005-0.05) mL:1 g.

[0039] Preferably, in step (3), the spraying speed is 1 to 100 g / min, and the flow speed of the ternary substrate is 200 to 1800 rpm.

[0040] Preferably, in step (3), the calcination temperature is 300-700° C., the calcination heating rate is 1-10° C. / min, the calcination atmosphere is air or oxygen, and the calcination time is 1-8 h.

[0041] A battery comprises the above-mentioned ternary positive electrode material with a core-shell structure.

[0042] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0043] (1) The present invention prepares a ternary positive electrode material with a core-shell structure, wherein the core layer is a ternary substrate LiNi x Co y Mn z O 2 , the shell is Li d MO, the core-shell structure prepared by the present invention improves the mechanical strength of the material, the shell layer can effectively protect the core layer substrate from being corroded by the electrolyte, and the shell layer has significantly better ion and electron conductivity due to the introduction of positive electrode micropowder, and the capacity and rate performance are improved to a certain extent.

[0044] (2) The present invention uses positive electrode micropowder as the raw material of the shell layer and uniformly coats it on the ternary substrate, which not only improves the performance of the ternary positive electrode material, but also avoids the waste of resources, environmental pollution and economic losses caused by the direct scrapping of the positive electrode micropowder, which will produce obvious economic benefits.

[0045] (3) The present invention firstly combines the positive electrode micropowder with metal nitrate by a low-temperature combustion method to obtain a light and fine composite oxide. This is because nitrate can react quickly at low temperatures and produce more gas, thereby obtaining a light and fine composite oxide. The composite oxide has a narrow particle size distribution and small and fluffy particles. Its fluffy and light weight is conducive to forming a uniform coating on the ternary positive electrode substrate. Then, the composite oxide is uniformly coated on the substrate through a spray coating process to obtain a core-shell structure coating layer, which solves the problem of easy agglomeration of micropowder during coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 XRD diffraction patterns of the core-shell structured ternary cathode materials prepared in Example 1 and Comparative Example 1 of the present invention;

[0047] Figure 2 This is a SEM image of the core-shell structured ternary cathode material prepared in Example 1 of the present invention;

[0048] Figure 3 The cyclic stability curves of the core-shell structured ternary cathode materials prepared in Example 1 and Comparative Example 1 of the present invention;

[0049] Figure 4 It is a rate performance curve diagram of the core-shell structured ternary positive electrode materials prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0050] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0051] Example 1

[0052] The structural formula of the core-shell structure ternary positive electrode material of this embodiment is: LiNi 0.8 Co 0.1 Mn 0.1 O 2 0.001[LiNi 0.5 Co 0.2 Mn 0.3 O 2 ·Li 2 (Co 2 Ce)O 8 ].

[0053] The method for preparing the core-shell structured ternary cathode material of this embodiment comprises the following specific steps:

[0054] (1) 96.56 g of particle size D50≤2 μm, molecular formula LiNi 0.5 Co 0.2 Mn 0.3 O 2 The ternary positive electrode powder was dispersed into 1000 mL of n-heptane oily liquid, and wet-grinded for 4 h at a rotation speed of 3000 rpm to obtain a powder suspension;

[0055] (2) 100 mL of the powder suspension prepared in step (1) was mixed with 100 mL of a 4 mol / L cobalt nitrate solution, 100 mL of a 2 mol / L cerium nitrate solution, 100 mL of a 2 mol / L lithium acetate / citric acid mixture, and 50 mL of a 2 mol / L hexamethylenetetramine solution, and ultrasonically stirred for 2 h to obtain an emulsion;

[0056] (3) The emulsion was placed in a water bath at 80°C to evaporate water and n-heptane to obtain a black viscous liquid, which was then placed in an oven at 120°C for drying for 24 hours to obtain a fluffy porous dry gel, which was then heated to 230°C and ignited. After intense combustion that lasted for tens of seconds, a fluffy composite oxide was obtained.

[0057] (4) The composite oxide was ultrasonically dispersed in 200 mL of 1 mol / L polyacrylamide dispersion, and ultrasonicated for 4 h to obtain a uniform suspension. The suspension was sprayed onto 97.278 kg of the ternary substrate LiNi at a high speed flow rate at a spray rate of 10 mL / min. 0.8 Co 0.1 Mn 0.1 O 2 Then, it is transferred to a box-type sintering furnace for calcination at a heating rate of 3°C / min, a calcination temperature of 600°C, a calcination time of 6h, and an oxygen atmosphere. After being taken out of the furnace, it is cooled and sieved to obtain a core-shell structured ternary positive electrode material.

[0058] Figure 2 This is an SEM image of the core-shell structured ternary positive electrode material prepared in Example 1 of the present invention; as can be seen from the figure, the diameter of the single crystal particles is about 3 μm, and the surface is coated with a layer of ternary micropowder and metal oxide composite structure, the coating layer is dense, and the micropowder is effectively fused to the surface of the substrate.

[0059] Example 2

[0060] The structural formula of the core-shell ternary material of this embodiment is: LiNi 0.8 Co 0.1 Mn 0.1 O 2 0.002[LiNi 0.5 Co 0.2 Mn 0.3 O 2 ·Li 2 (Co2 Ce)O 8 ].

[0061] The method for preparing the core-shell structure ternary material of this embodiment includes the following specific steps:

[0062] (1) 96.56 g of particle size D50≤2 μm, molecular formula LiNi 0.5 Co 0.2 Mn 0.3 O 2 The ternary positive electrode powder was dispersed into 1000 mL of n-heptane oily liquid, and wet-grinded for 4 h at a rotation speed of 3000 rpm to obtain a powder suspension;

[0063] (2) 100 mL of the powder suspension prepared in step (1) was mixed with 100 mL of a 4 mol / L cobalt nitrate solution, 100 mL of a 2 mol / L cerium nitrate solution, 100 mL of a 2 mol / L lithium acetate / citric acid mixture, and 50 mL of a 2 mol / L hexamethylenetetramine solution, and ultrasonically stirred for 2 h to obtain an emulsion;

[0064] (3) The emulsion was placed in a water bath at 80°C to evaporate water and n-heptane to obtain a black viscous liquid, which was then placed in an oven at 120°C for drying for 24 hours to obtain a fluffy porous dry gel, which was then heated to 230°C and ignited. After intense combustion that lasted for tens of seconds, a fluffy ultrafine composite oxide was obtained;

[0065] (4) The composite oxide was ultrasonically dispersed in 200 mL of 1 mol / L polyacrylamide dispersion, and ultrasonicated for 4 h to obtain a uniform suspension. The suspension was sprayed onto 48.639 kg of the ternary substrate LiNi at a high speed flow rate at a spray rate of 10 mL / min. 0.8 Co 0.1 Mn 0.1 O 2 Then transfer it to a box-type sintering furnace for calcination at a heating rate of 3°C / min, a calcination temperature of 600°C, a calcination time of 6h, and an oxygen atmosphere. After being taken out of the furnace, it is cooled and sieved to obtain a core-shell structured ternary positive electrode material.

[0066] Example 3

[0067] The structural formula of the core-shell ternary material of this embodiment is: LiNi 0.8 Co 0.1 Mn 0.1 O 2 0.005[LiNi 0.5 Co 0.2 Mn 0.3 O 2 ·Li 2 (Co 2 Ce)O8 ].

[0068] The method for preparing the core-shell structure ternary material of this embodiment includes the following specific steps:

[0069] (1) 96.56 g of particle size D50≤2 μm, molecular formula LiNi 0.5 Co 0.2 Mn 0.3 O 2 The ternary positive electrode powder was dispersed into 1000 mL of n-heptane oily liquid, and wet-grinded for 4 h at a rotation speed of 3000 rpm to obtain a powder suspension;

[0070] (2) 100 mL of the powder suspension prepared in step (1) was mixed with 100 mL of a 4 mol / L cobalt nitrate solution, 100 mL of a 2 mol / L cerium nitrate solution, 100 mL of a 2 mol / L lithium acetate / citric acid mixture, and 50 mL of a 2 mol / L hexamethylenetetramine solution, and ultrasonically stirred for 2 h to obtain an emulsion;

[0071] (3) The emulsion was placed in a water bath at 80°C to evaporate water and n-heptane to obtain a black viscous liquid, which was then placed in an oven at 120°C for drying for 24 hours to obtain a fluffy porous dry gel, which was then heated to 230°C and ignited. After intense combustion that lasted for tens of seconds, a fluffy ultrafine composite oxide was obtained;

[0072] (4) The composite oxide was ultrasonically dispersed in 200 mL of 1 mol / L polyacrylamide dispersion, and ultrasonicated for 4 h to obtain a uniform suspension. The suspension was sprayed onto a high-speed flowing 19.456 kg ternary substrate LiNi 0.8 Co 0.1 Mn 0.1 O 2 Then transfer it to a box-type sintering furnace for calcination at a heating rate of 3°C / min, a calcination temperature of 600°C, a calcination time of 6h, and an oxygen atmosphere. After being taken out of the furnace, it is cooled and sieved to obtain a core-shell structured ternary positive electrode material.

[0073] Comparative Example 1

[0074] The preparation method of the core-shell structured ternary positive electrode material of Comparative Example 1 comprises the following specific steps:

[0075] (1) 9.656 g of ternary positive electrode powder LiNi 0.5 Co 0.2 Mn 0.3 O 2 , 34.424g of cerium oxide, 83.926g of lithium hydroxide monohydrate were mixed, and then 9.728kg of ternary substrate LiNi 0.8 Co0.1 Mn 0.1 O 2 Mixing to obtain a coating material;

[0076] (2) The coated material is transferred to a box-type sintering furnace for calcination at a heating rate of 3°C / min, a calcination temperature of 600°C, a calcination time of 6 hours, and an oxygen atmosphere. After being taken out of the furnace, the material is cooled and sieved to obtain a core-shell structured ternary positive electrode material.

[0077] Figure 1 XRD diffraction patterns of the core-shell structured ternary cathode materials prepared in Example 1 and Comparative Example 1 of the present invention; it can be seen from the figure that the I(003) / I(104) intensity of Example 1 is higher and the layered structure is more complete.

[0078] Figure 3 The cyclic stability curves of the core-shell ternary cathode materials prepared in Example 1 and Comparative Example 1 of the present invention are shown in FIG. 1 ; the test voltage is 2.8 to 4.25 V, the test temperature is 25° C., and the cycle rate is 0.5 C for 80 cycles. Figure 3 It can be seen that Example 1 has a higher initial cycle capacity of 182.1 mAh / g, better cycle stability, and a capacity retention rate of 93.4% after 80 cycles.

[0079] Figure 4 The rate performance curve of the core-shell ternary cathode material prepared in Example 1 and Comparative Example 1 of the present invention; the test voltage is 2.8-4.25V, the test temperature is 25°C, the test rates are 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 0.1C, and each rate is cycled twice. Figure 4 It can be seen that Example 1 has better rate performance.

[0080] Table 1 shows the BET, compaction density and powder resistivity of Examples 1, 2, 3 and Comparative Example 1. As shown in Table 1, the ternary positive electrode materials prepared in Examples 1-3 have smaller BET, higher compaction density and lower powder resistivity. On the contrary, the powder resistivity of Comparative Example 1 is higher.

[0081] Table 1 BET (specific surface area), compaction density and powder resistivity of core-shell structured ternary cathode materials

[0082]

[0083] Table 2 shows the capacity data of Examples 1, 2, 3 and Comparative Example 1, with a test voltage of 2.8-4.25 V, a test ratio of 0.1 C, and a test temperature of 25° C. As shown in Table 2, compared with Comparative Example 1, the core-shell structure ternary positive electrode materials prepared in Examples 1 and 2 have higher capacity, while the capacity of Example 3 is lower, indicating that when the coating amount is too high, the material capacity will be affected.

[0084] Table 2 Capacity of core-shell structured ternary cathode materials

[0085] Electrochemical performance Example 1 Example 2 Example 3 Comparative Example 1 Charge specific capacity (mAh / g) 223.4 223.6 222.1 218.3 Discharge specific capacity (mAh / g) 202.6 202.1 199.4 190.9 Discharge efficiency (%) 90.7 90.4 89.8 87.4

[0086] The present invention is not limited to the above-mentioned embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A ternary cathode material with a core-shell structure, characterized in that: The chemical formula of the core-shell structured ternary cathode material is LiNi x Co y Mn z O2·wLi d MO, the core layer of the core-shell structured ternary positive electrode material is LiNi x Co y Mn z O2, Li shell d MO; wherein M is (Ni a Co b Mn c ) k A 1-k , wherein A includes cobalt and cerium; wherein 0.3≤x≤1, y>0, z>0, and x+y+z=1, 0.3≤a≤1, b≥0, c≥0, and a+b+c=1, 1≤d≤3, 0 <k≤0.5,0.01%≤w≤2%; The method for preparing the core-shell structured ternary cathode material comprises the following steps: (1) Dispersing the positive electrode powder in an organic solvent, grinding it, adding nitrate, organic acid and surfactant, stirring and emulsifying it to obtain an emulsion; (2) evaporating and drying the emulsion to obtain a fluffy porous dry gel, and heating and igniting the dry gel to obtain a fluffy composite oxide; (3) dispersing the composite oxide in an organic dispersion, spraying and coating the composite oxide on a ternary substrate, and calcining the composite oxide to obtain the core-shell structured ternary cathode material; The surfactant is at least one of hexamethylenetetramine, sodium dodecylbenzenesulfonate, and hexadecyltrimethylammonium bromide; The positive electrode fine powder has a D50 of 0.1 to 1 μm and a D99 of 0.3 to 2 μm.

2. The core-shell structured ternary cathode material according to claim 1, characterized in that: 0.3≤x≤0.6, 0.6≤a≤0.

8.

3. The core-shell structured ternary cathode material according to claim 1, characterized in that: The core-shell structured ternary cathode material is LiNi 0.8 Co 0.1 Mn 0.1 O2 · 0.001[LiNi 0.5 Co 0.2 Mn 0.3 O2·Li2(Co2Ce)O8]、LiNi 0.8 Co 0.1 Mn 0.1 O2 · 0.002[LiNi 0.5 Co 0.2 Mn 0.3 O2·Li2(Co2Ce)O8]、LiNi 0.8 Co 0.1 Mn 0.1 O2 · 0.005[LiNi 0.5 Co 0.2 Mn 0.3 At least one of [O2·Li2(Co2Ce)O8].

4. The method for preparing the core-shell structured ternary cathode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Dispersing the positive electrode powder in an organic solvent, grinding it, adding nitrate, organic acid and surfactant, stirring and emulsifying it to obtain an emulsion; (2) evaporating and drying the emulsion to obtain a fluffy porous dry gel, and heating and igniting the dry gel to obtain a fluffy composite oxide; (3) dispersing the composite oxide in an organic dispersion, spraying and coating the composite oxide on a ternary substrate, and calcining the composite oxide to obtain the core-shell structured ternary cathode material; The surfactant is at least one of hexamethylenetetramine, sodium dodecylbenzenesulfonate, and hexadecyltrimethylammonium bromide; The positive electrode fine powder has a D50 of 0.1 to 1 μm and a D99 of 0.3 to 2 μm.

5. The preparation method according to claim 4, characterized in that: The nitrate is cobalt nitrate or cerium nitrate.

6. The preparation method according to claim 4, characterized in that: In step (1), the organic acid is one of lithium acetate and citric acid.

7. The preparation method according to claim 4, characterized in that: In step (2), the temperature of the heating and ignition is 200-400°C, and the atmosphere of the heating and ignition is air.

8. The preparation method according to claim 4, characterized in that: In step (3), the chemical formula of the ternary substrate is LiNi x Co y Mn z O2, where 0.3≤x≤1, y>0, z>0, and x+y+z=1.

9. The preparation method according to claim 4, characterized in that: In step (3), the organic dispersion is at least one of a polyacrylamide solution, a hydrolyzed polymaleic anhydride solution, a polyethylene glycol 200 solution, and a polyethylene glycol 400 solution.

10. A battery, characterized in that: A ternary positive electrode material comprising a core-shell structure as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Preparation method of cladding material of lithium ion battery

    CN103915629A

  • Low-temperature burning preparation method and positive electrode material of spinel lithium nickel manganese oxide

    CN108649208A

  • Method for preparing lithium-rich positive electrode material through adjustable low temperature combustion method

    CN108832085A

  • Core-shell high-nickel monocrystal nickel cobalt lithium manganate positive electrode material and preparation method and application thereof

    CN110165193A